Anatomical Variations of Lumbar Arteries and Their Clinical Implications: A Cadaveric Study. (12th September 2013) - Karunanayake, Aranjan Lionel; Pathmeswaran, Arunasalam
Abstract : Lumbar arteries arise from the abdominal aorta. Some abdominal and spinal surgeries can damage these arteries, and that can lead to serious consequences. This study aimed at studying the types and frequencies of variations of lumbar vasculature. We dissected both sides of 109 adult human cadavers and studied the variations of lumbar vasculature. Age range was 43–90 years. Fifty-seven percent were males and 43% were females. The number of lumbar arteries arising from either side of the abdominal aorta varied between 3 and 5 pairs. The lumbar arteries arose from a common single stem in 12% of the cadavers. The third and fourth pairs of lumbar arteries arose from a common single stem in 3% and 11% of cadavers, respectively, and the first and second pairs of lumbar arteries arose from a common single stem in 1% and 2% of cadavers, respectively. The first and second lumbar arteries on the right side traveled anterior to the right crus of the diaphragm in 7% and 8% of cadavers, respectively. There were several variations with regard to the number, origin from the abdominal aorta, and pathway of lumbar arteries from what is described in the literature.